Chin Lurus Enterprise: A charity business? - Mhd. Sarif, Suhaimi (2020)
Chin Lurus Enterprise case postulates that a small business could incorporate Corporate Social Responsibility (CSR) perspectives in providing services to the 300 households in his village. There is a need to balance between business and charity. Chin Lurus Enterprise needs to secure its bottomline affordability by having sufficient funds to operate the business. When the business is unable to secure sufficient funds to operate, it will not be able to meet both its economic and social ends. The CSR is also demonstrated by Chin Lurus Enterprise when a due respect given to employees as an investment in personnel development and preventive mechanism to avoid conflict at the workplace.